TIME PREFERENCE: THE PERSPECTIVE OF THE AUSTRIAN SCHOOL AND A DEBATE ON THE HYPERBOLIC DISCOUNT - Dutra Macedo, Manoela (REVISTA PROCESOS DE MERCADO, 2022)
Abstract: From the central axiom of human action is deduced the universal law of time preference: the individual prefers that his ends be reached in the shortest possible time, he prefers to consume in the present than to consume in the future. From the difference between the value that the individual attributes to a good in the present and to the same good in the future, the interest rate emerges as a fundamental element of the intertemporal coordination of the economy. From the theoretical framework of the Austrian School, this paper discusses the hyperbolic discount model, proposed by the Behavioral Economics, as a way of describing time preference. This paper emphasizes that for an adequate intertemporal allocation of resources to occur, the interest rate that allows efficient intermediation between savers and investors and its calculation formula must be discovered through voluntary transactions in the market. Keywords: Austrian School; time preference; interest rate; Behavioral Economics; hyperbolic discounting. JEL Classification: B53; D01; E43.